Peran kepemimpinan dalam membawa perubahan pada organisasi dakwah - Syahrizal (Al-Manaj : Jurnal Program Studi Manajemen Dakwah, 2025)
Leaders in missionary organizations play an important role as agents of change. This is due to the leadership position being at the forefront and the highest regarding matters pertaining to the flow of the missionary organization. The results show that in carrying out this role as agents of change, leaders initiate the change process by making decisions. All activities carried out within a missionary organization are known to be based on decisions that have been mutually agreed upon by the leaders. Next is providing motivation, which means leaders are able to inspire the enthusiasm of the members through motivation, whether by giving rewards or, conversely, through threats that lead to positive outcomes. The following step is in the process of communication networking, meaning that leaders are required to establish good communication networks with the members of the missionary organization. Finally, in the accountability process, it involves being responsible